Technical Inefficiency in Nine Clusters of Indonesian Manufacturing Firms And its Determinants: Stochastic Frontier Analysis - Theresya Jeini Astanto; Suyanto - Suyanto; Henrycus Winarto Santoso; Ruhul Salim (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2022)
The current study examines the technical inefficiency of Indonesian manufacturing firms and its key determinants. Extending the previous research that mainly focuses on firms in a specific industry, the current study groups firms into nine industrial clusters and estimates them separately to find a variety of results among the clusters. The stochastic frontier analysis (SFA) method is applied to estimate the inefficiency score and the key determinants of 5,848 firms for five years (29,240 total observations). Data period ended in 2014 due to the substantial change in the classification code of the manufacturing industry in the survey by the Indonesian Central Board of Statistics. Five notable findings are recorded. First, the average efficiency score of all observed firms is 0.8815. Second, firm size is found to have a negative effect on inefficiency in the sample of all firms and three out of nine clusters (ISIC 34, ISIC 35, and ISIC 37). Third, foreign ownership generates a negative contribution to firms’ technical inefficiency in both the sample of all firms and the sample of each nine industrial clusters. Fourth, export orientation has various effects on firms across nine industrial clusters, with a dominant significant negative impact in paper and paper product industry (ISIC 34) and metal product industry (ISIC 38). Finally, import intensity provides a significant negative impact on firms in most industrial clusters. These findings support the argument on the importance of absorption capacity and unique firm characteristics in analyzing the impact of key determinants of technical inefficiency.